EFFECT OF EXERCISE AND METHOD OF SKILL JUMPING togok FLEXIBILITY SMASH BADMINTON - KUSUMA, DANANG ADHI (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2019)
The purpose of this study to determine: (1) Badminton smash jumping skill difference between the model and the model plaiometrik exercise circuit training. (2) The interaction between the model with flexibility exercises togok  against jumping smash badminton skills. (3) The difference between the skills of jumping smash badminton plaiometrik practice models and models of circuit training for athletes who have a high togok  flexibility. (4) The difference between the skills of jumping smash badminton plaimetrik practice models and models of circuit training for athletes who have a low togok  flexibility.The research was conducted at the Badminton courts of the Faculty of Education Universitas Tunas Pembangunan Surakarta. The method used is an experiment with a 2x2 factorial design. The research variables consisted of five variables: the independent variable plaiometrik training method and circuit training method, namely flexibility togok  attributive variable high and low togok  flexibility, as well as the dependent variable jumping smash bulutangkis. The samples were 50 people from 50 students of coaching badminton achievement FKIP UTP Surakarta. Test data collection techniques and test measurement instruments. Technique of data analysis of variance (Anova) in both directions and test Lilliefors (Sudjana, 1992: 466-468)The results of the data analysis performed using two-way Anova can either (1) Differences smash jumping skills with training methods plaiometrik badminton and circuit training method. (2) the interaction between the practice and flexibility togok  against jumping smash badminton skills. (3) The difference in skills training methods plaiometrik smash jumping and circuit training method for athletes who have a high togok  flexibility. (4) Difference smash jumping skills training methods plaiometrik and circuit training method for athletes who have a low togok  flexibility.